Variability of euphausiid larvae densities during the 2011, 2012, and 2014 summer seasons in the Atlantic sector of the Antarctic - Rombola, Emilce Florencia; Franzosi, Claudio Atilio; Tosonotto, Gabriela Viviana; Alder, Viviana Andrea; Marschoff, Enrique Ricardo (Polar Science)
Euphausiid larvae were collected in the Weddell Scotia Confluence region in summer 2011, in the West Antarctic Peninsula and Scotia Sea in 2012, and in the South Orkneys Shelf in 2014. From 2011 to 2014 the larval stages geographic distribution and the distribution of water masses were consistent with published information. The densities observed were compared between the cruises and with the 1981 and 1995 values by means of a kernel estimate of absolute and relative densities at a fixed grid of points. The values of Thysanoessa macrura were higher in 2011 and 2012 and those of Euphausia superba were lower than those observed in 1981 and 1995. Euphausia frigida did not show significant variations in absolute density but their relative values were higher than those of E. superba. No significant variations were observed in absolute values between 1981 and 1995. The opposite pattern was found in 2014, with significantly higher densities of E. superba than those of T. macrura. No single factor could be identified to explain these variations in density, suggesting the existence of complex mechanisms coupling the reproductive biology with oceanographic phenomena. Their description will require ample spatial and temporal monitoring rather than locally detailed observations. Fil: Rombola, Emilce Florencia. Ministerio de Relaciones Exteriores, Comercio Interno y Culto. Dirección Nacional del Antártico. Instituto Antártico Argentino; Argentina. Consejo Nacional de Investigaciones Científicas y Técnicas; Argentina Fil: Franzosi, Claudio Atilio. Ministerio de Relaciones Exteriores, Comercio Interno y Culto. Dirección Nacional del Antártico. Instituto Antártico Argentino; Argentina Fil: Tosonotto, Gabriela Viviana. Ministerio de Relaciones Exteriores, Comercio Interno y Culto. Dirección Nacional del Antártico. Instituto Antártico Argentino; Argentina Fil: Alder, Viviana Andrea. Ministerio de Relaciones Exteriores, Comercio Interno y Culto. Dirección Nacional del Antártico. Instituto Antártico Argentino; Argentina. ...